Analisis Keefektivitasan Penerapan Enterprise Resources Planning berbasis System Application Product dalam Pengendalian Logistik Bank - Rahayu, Norra Isnasia; Hakim, Farhadiba; Perdana, Riky; Firdiansyah Arief, Ronny (Akuntansi & Ekonomika, 2025)
This study analyzes the effectiveness of implementing SAP-based ERP in logistics control in the banking sector, with a specific case study at PT. Bank Rakyat Indonesia (Persero) Tbk. Lancang Kuning Branch Office. Using a qualitative descriptive approach through interviews, this study compares logistics control practices before and after SAP implementation. The results show that SAP adoption significantly improves transparency, accountability, and efficiency in logistics reporting. Before implementation, the logistics system tended to be fragmented and less transparent, causing delays and susceptibility to human error and data manipulation. Post-SAP, logistics reports become more detailed, transparent, integrated in real time between departments, and support faster audit processes. These findings emphasize the crucial role of SAP-based ERP in realizing more effective and efficient logistics control, as well as improving company performance in the modern banking environment.